Identifying Children Potentially at Risk of Abuse at the Emergency Setting: A Qualitative Study on Healthcare Professionals - Anne Noor Sri Juwaneeta Jamaludin; Jennifer Anne Oxley; Quek Kia Fatt (Public Health, 2025)
ObjectiveTo examine the current indicators used by medical healthcare professionals to identify the intent of child injury and the processes that are undertaken once potential child neglect, maltreatment or abuse is identified.Materials and MethodsThirty in-depth interviews were conducted at the ETD in three major hospitals in the Klang Valley, Malaysia which consists of specialists, medical officers, nurses and medical assistants.ResultsThe study found that there is a significant gap identified in medical professionals’ knowledge and skills related to understanding, identifying and detecting child abuse and neglect (CAN), particularly among medical officers who are in charge of diagnosis and reports in the hospital.ConclusionThere is a need to provide more comprehensive and specific training for medical health professionals in the emergency department (ED) regardless of their level and status. This will enhance their understanding on identifying children at risk of abuse. The need for a proper and standardized screening tool for identification is utmost important if all children attending ED is being screened.KeywordsChild abuse and neglect (CAN); Emergency department (ED); Qualitative study; Healthcare professionals; Non-accidental injuries.AbbreviationsCAN: Child Abuse and Neglect; ED: Emergency Department; SCAN: Suspected Child Abuse and Neglect; OSCC: One-Stop Crisis Centre; SOPs: Standard Operating Procedures; GPs: General practitioners.